(untitled) (Journal of Hama University, 2022)
Amputations are motor disabilities facing sensitive and complex problems such as the emergence of many psychological and social problems, so the current descriptive study was conducted to assess social support and its relationship to the level of satisfaction with the quality of life of a sample of users of alternative limbs consisting of 100 casualties in Zahi Azraq Military Hospital and selected in the intentional manner, The data were collected using a questionnaire developed based on the Al-Hindawi study scale. The results showed that overall social support was high and